2013
DOI: 10.1155/2013/518170
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor Impairment and Restoration on Optical Coherence Tomographic Image

Abstract: With recent development of spectral-domain optical coherence tomography (SD-OCT), the pathological changes of retina can be observed in much greater detail. SD-OCT clearly delineates three highly reflective lines in the outer retina, which are external limiting membrane (ELM), photoreceptor inner and outer segment (IS/OS) junction, and cone outer segment tips (COST) in order from inside. These lines can serve as hallmarks for the evaluation of photoreceptor condition. In retinitis pigmentosa (RP) leading to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 30 publications
6
76
0
3
Order By: Relevance
“…Under favorable conditions, rod and cone OSs are capable of regrowth-for example, following light-induced damage (15), retinal detachment (16), or macular hole surgery (17). However, the extent and time course of regrowth depend on the severity of the damage (15).…”
Section: Discussionmentioning
confidence: 99%
“…Under favorable conditions, rod and cone OSs are capable of regrowth-for example, following light-induced damage (15), retinal detachment (16), or macular hole surgery (17). However, the extent and time course of regrowth depend on the severity of the damage (15).…”
Section: Discussionmentioning
confidence: 99%
“…One reason was that some eyes with relatively intact EZ lines had reduced mfERG amplitudes. It was the abnormality of the IZ line that led to reduced mfERG amplitudes, while the EZ line was intact in OCT images [34]. A second possibility was that the functional abnormality preceded the structural changes in RP eyes.…”
Section: Photoreceptor Segmentsmentioning
confidence: 99%
“…A number of studies have directed particular attention towards central foveal thickness (CFT) [3,[8][9][10][11][12][13][14][15][16], and several studies have found a correlation between a reduced CFT and better postoperative visual acuity [3,14,16], while others have not [7,8,15]. Numerous studies have also found that an intact preoperative ellipsoid zone (previously known as the inner/outer segment junction line) [17] is significantly correlated with better postoperative visual acuity [6,7,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%